Evaluation of the genotoxic potential of the isocoumarin paepalantine in in vivo and in vitro mammalian systems - Tavares, D. C.; Varanda, Eliana Aparecida [UNESP]; Andrade, FDP; Vilegas, Wagner [UNESP]; Takahashi, C. S. (Elsevier B.V., 1999)
Paepalantine is an isocoumarin isolated from Paepalanthus vellozioides which showed antimicrobial activity in in vitro experiments. In the present study, paepalantine was tested for possible clastogenic and cytotoxic action. Cultures from different individuals were treated with paepalantine at concentrations of 20, 40 and 80 mu g/ml. The effect of isocoumarin was also tested in an in vivo assay using Wistar rat bone marrow cells. Paepalantine was administered intraperitoneally at concentrations of 6.25, 12.5 and 25 mg/kg body weight. Under these conditions paepalantine did not have a clastogenic effect, but was significantly cytotoxic in the in vitro and in vivo mammalian cell systems tested in the present work. (C) 1999 Elsevier B.V. Ireland Ltd. All rights reserved.
Keywords: paepalantine; isocoumarin; chromosomal aberrations; cytotoxicity